Onychomycosis: dermatophytes to yeasts: an experience in and around Mumbai, Maharashtra, India - Suryawanshi, Rupali S.; Wanjare, Shashir W.; Koticha, Avani H.; Mehta, Preeti R. (International Journal of Research in Medical Sciences, 2017)
Background: Onychomycosis is a fungal nail infection having wide range of prevalence in different geographical regions. It becomes imperative to know prevalent causative agent in local area to improve quality of life of patients. Present study was aimed to study epidemiological, clinical and laboratory aspects of onychomycosis Methods: Study was carried out prospectively at a tertiary care teaching hospital Nail scrapings of 630 clinically suspected cases of onychomycosis over a period of 5 years (January 2012 to December 2016) were subjected to KOH examination and culture. Results: Young adults in age group of 21-40 years (67.61%) were predominantly affected with male to female ratio of 1.8:1. Overall prevalence of onychomycosis of the present study is 58.41%. Yeasts were isolated in 47.86%, dermatophytes in 30.71% and non dermatophytic filamentous fungi in 21.43% Conclusions: Present study demonstrates a shift in causative agents from dermatophytes to yeasts.